Inventory of Medicinal Plants at Jompie Botanical Garden in Parepare City - Indryani, Andi Fika; Muis, Abd.; Syamsiah, Syamsiah; Kurnia, Nani (Jurnal Biologi Tropis, 2024)
The inventory of medicinal plants involves the recording and registering of medicinal plant species. This research aims to identify the species of medicinal plants found in Jompie Botanical Garden, Parepare City, and to understand how the local community utilizes these plants. The methodology employed is exploratory and descriptive. The study was conducted from January to February 2024 at Jompie Botanical Garden, Parepare City. The subjects of this research are the plant species used by the local community for medicinal purposes and the methods of utilizing these plants. Data collection was carried out through observation, interviews, and documentation. The collected data were analyzed by compiling the identified plant characteristics, medicinal properties, and utilization methods into tables and photographs, followed by descriptive explanations. The research findings indicate that 40 plant species are used by the local community in Jompie Botanical Garden for medicinal purposes. The plant parts utilized include roots, stems, leaves, fruits, and flowers, with leaves being the most commonly used. The plants are processed into medicine through various methods, such as boiling, grinding, grating, squeezing, cutting, and chewing, with boiling being the most common technique.